2002
DOI: 10.1002/eat.10104
|View full text |Cite
|
Sign up to set email alerts
|

Self‐harm and substance use in a community sample of Black and White women with binge eating disorder or bulimia nervosa

Abstract: Objective: This study evaluated rates of self-harm and substance use in women with either bulimia nervosa (BN) or binge eating disorder (BED) and assessed whether differences in self-harm and substance use are related to sexual or physical abuse. Method: Alcohol abuse, self-harm, and use or abuse of various illicit drugs were evaluated in a sample of 53 women with BN and 162 women with BED. Results: Self-harm and substance use generally did not differentiate BED and BN cases, but rates of self-harm and substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 24 publications
3
30
0
3
Order By: Relevance
“…countries (Garner et al 1985;Yellowlees, 1985;Mitchell et al 1986;Gleaves & Eberenz, 1993;Pryor et al 1996;Tobin & Griffing, 1996;Wiederman & Pryor, 1996a, b;Favaro & Santonastaso, 1997, 1998Nagata et al 2000a;Steiger et al 2001;Anderson et al 2002;Dohm et al 2002;Paul et al 2002;Stein et al 2004;Ruuska et al 2005;Corstorphine et al 2007;Ahren-Moonga et al 2008;Bulik et al 2008;Fichter et al 2008;Muehlenkamp et al 2009;Liang & Meg Tseng, 2011;Peebles et al 2011;Iannaccone et al 2013;Vansteelandt et al 2013;Bueno et al 2014). The 29th publication (Solano et al 2005) shared participants with the sample in Bueno et al (2014).…”
Section: Search Resultsmentioning
confidence: 99%
“…countries (Garner et al 1985;Yellowlees, 1985;Mitchell et al 1986;Gleaves & Eberenz, 1993;Pryor et al 1996;Tobin & Griffing, 1996;Wiederman & Pryor, 1996a, b;Favaro & Santonastaso, 1997, 1998Nagata et al 2000a;Steiger et al 2001;Anderson et al 2002;Dohm et al 2002;Paul et al 2002;Stein et al 2004;Ruuska et al 2005;Corstorphine et al 2007;Ahren-Moonga et al 2008;Bulik et al 2008;Fichter et al 2008;Muehlenkamp et al 2009;Liang & Meg Tseng, 2011;Peebles et al 2011;Iannaccone et al 2013;Vansteelandt et al 2013;Bueno et al 2014). The 29th publication (Solano et al 2005) shared participants with the sample in Bueno et al (2014).…”
Section: Search Resultsmentioning
confidence: 99%
“…55,75,78,82,83 This suggests that weight and shape overconcern may be sufficiently elevated to be considered as a diagnostic criterion for BED as it is for BN. Even though BED does not currently have a cognitive criterion concerning shape and weight concern, future versions of the DSM (e.g., DSM-V) could consider stipulating that self-evaluation is unduly influenced by body shape and weight in BED.…”
Section: Distinguishing Bed From Bnmentioning
confidence: 99%
“…For example, high rates of co-morbidity between NSSI and substance use are commonly reported (Putnins, 1995;Beutrais et al, 1996;Kessler et al, 1999;Hilt et al, 2008), although not invariably found (Dulit et al, 1994;Soloff et al, 1994). There is also a well-documented link between NSSI and eating disorders (Favazza et al, 1989;Favaro and Santonastaso, 2000;Wonderlich, 2001;Dohm, 2002;Paul, 2002;Sansone and Levitt, 2002;Stein et al, 2004; but see also Zlotnick et al, 1999). Rates of self-injury are also elevated six-fold in people who have been exposed to physical acts of violence or threats to their lives (Berenson et al, 2001).…”
mentioning
confidence: 99%